2015
DOI: 10.1136/bjsports-2015-094935
|View full text |Cite
|
Sign up to set email alerts
|

Early functional rehabilitation or cast immobilisation for the postoperative management of acute Achilles tendon rupture? A systematic review and meta-analysis of randomised controlled trials

Abstract: Compared to traditional ankle immobilisation, with a non-weight bearing cast following surgical repair of acute Achilles tendon rupture, early dynamic functional rehabilitation is as safe with higher patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
91
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 30 publications
4
91
1
7
Order By: Relevance
“…When surgery is performed, traditional postoperative protocols involved an extended period of ankle immobilisation in a rigid cast after surgery3 (casting) to enable sufficient tissue healing to reduce the risk of rerupture. However an extended period of immobilisation carries the risk of adhesions and muscular atrophy, these competing risks must be balanced to provide optimal clinical care 4. More recently, studies have shown that early postoperative ankle motion and functional rehabilitation (bracing) may not increase in the rate of rerupture 5…”
Section: Introductionmentioning
confidence: 99%
“…When surgery is performed, traditional postoperative protocols involved an extended period of ankle immobilisation in a rigid cast after surgery3 (casting) to enable sufficient tissue healing to reduce the risk of rerupture. However an extended period of immobilisation carries the risk of adhesions and muscular atrophy, these competing risks must be balanced to provide optimal clinical care 4. More recently, studies have shown that early postoperative ankle motion and functional rehabilitation (bracing) may not increase in the rate of rerupture 5…”
Section: Introductionmentioning
confidence: 99%
“…This is an important area and a decline in the rate of surgery for Achilles tendon ruptures has been reported [4]. Functional rehabilitation has been described in a number of papers [5,6] and generally refers to an orthosis that permits weight bearing, but does not necessarily allow for movement at the ankle. Functional bracing is described within the literature but has not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…This phrase usually applies to a weight bearing orthosis but does not always indicate whether the device permits movement at the ankle. Functional Bracing may include dynamic bracing, rigid dorsal split, removable cast boot or semi-rigid wrap [6]. There are a number of studies investigating functional rehabilitation following surgery for Achilles tendon rupture [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu nedenle, akut Aşil tendon rüptürünün cerrahi onarımını takiben erken fonksiyonel rehabilitasyonun güvenli olduğu ve daha yüksek hasta memnuniyeti ve daha erken işe dönüş sağladığı sonucuna varmışlardır. [14] …”
unclassified